PENERAPAN AKUAPONIK UNTUK MENJAGA KETAHANAN PANGAN DI DESA CIOMAS KABUPATEN BOGOR - Muhammad Andhika Maulana Kusnadi; Khadijah Nurul Lathifah; Farrah Zulfa; Rifki Adam Firdaus; Lely Romandhani; Sabrina Nurul Arifah; Aditya Dwi Prasetyo Wibowo; Fikri Fadila; Lutfi Hanafi; Hafizhah Farahiyati Ananda (Yayasan Education and Social Center, 2022)
The Covid-19 pandemic has had many negative impacts on the income of the Indonesian residents, one of them are Ciomas village residents who are mostly engaged in micro, small and medium enterprises (MSMEs). One of these impacts was felt by the owner of abon catfish MSMEs in Ciomas Village, which production decreased after the pandemic. Raw materials which is large catfish are difficult to obtain because of the high cost in catfish cultivation. Aquaponics activities are intended to cultivate fish and plants in one environment as well as being symbiotic. The aquaponics installation is installed in the resident's pond by installing a pipe containing rockwool and water spinach seeds which are connected to a water pump with an up-flow system. Obstacles faced during the activity are difficulties in pipes installing, leaking ponds, not suitable water pumps used, and time limits. Further monitoring needs to be done to see the development of aquaponics because the water used comes from household water drainage which has the potential to hinder the success of the aquaponics activity